Quasiparticle and optical properties of strained stanene and stanane - Pengfei Lu (Nature Portfolio, 2017)
Abstract Quasiparticle band structures and optical properties of two dimensional stanene and stanane (fully hydrogenated stanene) are studied by the GW and GW plus Bethe–Salpeter equation (GW-BSE) approaches, with inclusion of the spin-orbit coupling (SOC). The SOC effect is significant for the electronic and optical properties in both stanene and stanane, compared with their group IV-enes and IV-anes counterparts. Stanene is a semiconductor with a quasiparticle band gap of 0.10 eV. Stanane has a sizable band gap of 1.63 eV and strongly binding exciton with binding energy of 0.10 eV. Under strain, the quasiparticle band gap and optical spectrum of both stanene and stanane are tunable.